Ethnomedicine and Medicinal Plant Conservation Study in the Oben Village Community, Nekamese District, Kupang Regency - Sabaat, Jeanet Anggiany; Muntasir, Muntasir; Purnasari, Cahyani (Jurnal Biologi Tropis, 2026)
Ethnomedicine represents indigenous knowledge regarding the use of medicinal plants for healthcare and plays an important role in supporting biodiversity conservation. However, documentation of ethnomedicinal knowledge in Oben Village, Nekamese District, Kupang Regency, remains limited, creating a risk of knowledge erosion across generations. This study aimed to document medicinal plant diversity, traditional utilization patterns, and community-based conservation practices in Oben Village. A descriptive qualitative approach was employed involving 30 purposively selected respondents. Data were collected through interviews, field observations, and documentation, and analyzed descriptively. A total of 44 medicinal plant species belonging to various families were identified and used to treat 20 categories of diseases. Leaves were the most frequently utilized plant part (55%), while boiling was the predominant preparation method (66%), followed by oral administration as the primary mode of use. The community also applies multi-species herbal formulations for certain ailments, reflecting a rich body of local therapeutic knowledge. Conservation is primarily conducted through home gardens, mixed cropping systems, and the sustainable use of naturally growing plant resources. These findings highlight the richness of local ethnomedicinal knowledge and demonstrate its contribution to both primary healthcare and in situ plant conservation. The documented information provides a scientific basis for biodiversity conservation, preservation of indigenous knowledge, and future pharmacological investigations of medicinal plant resources.